2005
DOI: 10.1038/sj.gene.6364164
|View full text |Cite
|
Sign up to set email alerts
|

IFNG polymorphisms are associated with gender differences in susceptibility to multiple sclerosis

Abstract: Interferon-gamma (IFNg) treatment is deleterious in multiple sclerosis (MS). MS occurs twice as frequently in women as in men. IFNg expression varies by gender. We studied a population-based sample of US MS patients and ethnicity-matched controls and independent Northern Irish and Belgian hospital-based patients and controls for association with MS, stratified by gender, of an intron 1 microsatellite [I1 (761)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 80 publications
3
32
0
Order By: Relevance
“…Alternatively, genetic variants that affect expression or function of IFNγ might influence the susceptibility to MS and severity of the disease. Weinshenker and colleagues showed that being a carrier of the A allele of a 3′(325)*G→A single nucleotide polymorphism just 3′ to the IFNG gene is associated with increased susceptibility to MS in men (Kantarci et al, 2005). More recently, we have shown that this polymorphism is associated with decreased IFNγ protein and mRNA expression in men with MS (Kantarci et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively, genetic variants that affect expression or function of IFNγ might influence the susceptibility to MS and severity of the disease. Weinshenker and colleagues showed that being a carrier of the A allele of a 3′(325)*G→A single nucleotide polymorphism just 3′ to the IFNG gene is associated with increased susceptibility to MS in men (Kantarci et al, 2005). More recently, we have shown that this polymorphism is associated with decreased IFNγ protein and mRNA expression in men with MS (Kantarci et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…An increasing number of reports have pointed to sex-specific association of common gene polymorphisms with autoimmunity. For instance, CD95 was found to be associated with susceptibility to MS in women (Kantarci et al, 2004a), APOE with disease severity of MS in women (Kantarci et al, 2004b), IFNG with susceptibility to MS in men (Goris et al, 2002;Kantarci et al, 2005) and IL26 with susceptibility to RA in women (Vandenbroeck et al, 2003). These data call for a systematic whole-genome scrutiny for gender-specific autoimmune susceptibility factors.…”
Section: Discussionmentioning
confidence: 96%
“…The protective effect of IFN-␤ therapy in MS patients has been attributed, at least in part, to down-regulation of IFN-␥ production (73). Myelin Ag-induced IFN-␥ production is more efficient in female MS patients as compared with males (74). MS patients treated with systemic IFN-␥ had a dramatic worsening of the disease (75).…”
Section: Discussionmentioning
confidence: 99%